Pelatihan Integrasi Kecerdasan Buatan dan Deep Learning untuk Mengembangkan Peran Guru dalam Pembelajaran - Tina Sri Sumartini; Maulida Aulia Rahman; Salma Hasna Arumaisya (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to develop teachers’ abilities in integrating artificial intelligence (AI) and deep learning. The activity was conducted at SMK Al-Hikmah on Wednesday, July 23, 2025, and was attended by 23 teachers from various subject areas. The implementation method took the form of an interactive workshop that included material presentations, discussions, hands-on practice, and a post-test. The evaluation results showed an average score of 90.87, a median of 95, and a score range of 65–100. This indicates that most teachers have understood the basic concepts of AI, recognized its ethical implications, and demonstrated the ability to implement the technology in teaching. The high achievement of participants reflects the great potential of AI in supporting adaptive learning and personalized instruction, although a small number of teachers still require additional assistance in technical aspects. This training emphasizes that AI integration is not a replacement for the teacher’s role, but rather a reinforcement of the teacher’s function as a facilitator and learning guide. The outcomes of this activity can serve as a foundation for follow-up mentoring programs and teacher capacity development in addressing the challenges of 21st-century education.